Farmers’ Perceptions on the Adoption of Environment-Friendly Pepper Production Methods in Malaysia - Wong, See Keong; Shamsudin, Mad Nasir (2009)
This study investigates the farmers’ perceptions on the adoption of environment-friendly pepper production methods in Malaysia. This piece of information is deemed useful and important for the policy makers in Malaysia to devise appropriate policies to help Malaysian pepper farmers to have continuous market access in the gradually competitive international market arena. For this purpose, besides semi-structured interviews conducted on a random sample of 100 pepper farm households throughout Sarawak, structured questionnaires were also distributed to 31 literate pepper farmers randomly sampled in Sarawak between 1999 and 2007, to gather information regarding farmers’ perceptions on the adoption of environment-friendly pepper production methods in Malaysia. The results from the survey indicated that pepper farmers in Malaysia were generally less proactive and would take no initiative to produce environment-friendly pepper if there were no mandatory requirements from the government on these pepper farmers to curtail the use of chemical fertilizers and pesticides in their pepper cultivation ventures. There is an urgent need for Malaysian government to promulgate relevant policies to be integrated in the pepper production handbook or guidelines to make it mandatory for pepper farmers in Malaysia to minimize or even totally eliminate the use of chemical inputs in their pepper production processes.